Nasionalisme vs Globalisasi ‘Hilangnya’ Semangat Kebangsaan dalam Peradaban Modern - Grendi Hendrastomo * (Dimensia: Jurnal Kajian Sosiologi, 2007)
This article is going to discuss about the conflict between nationalism and globalization in Indonesia. The focus of this article will be more illuminated on the decreasing of causal factor of nationalism. Nationalism in Indonesia is fading sooner or later and will be replaced by the arousal of ethnicities and globalism. There is a tendency to give more priority to their group’s importance and superiority more than what they give to their countries. Beside from the strengthening of ethnicities, openness and modernity which are the products of globalization are undermining our nationalism. This article will also describe the perspective of world as a global villages where world is as part of the globalization in where the interaction among person is as if it is borderless. Keywords: Nationalism, Globalisation, Ethnicities, Imagined Community.